Le père rejeté, le père rejetant chez Hervé Guibert et Yves Navarre - Porumb, Anca (Romanica Silesiana)
The first-person narrative novels, Mes parents by Hervé Guibert and Biographie I, II by Yves Navarre, are part of the characters’ crisis writing where the reason of evil is always the father’s presence. Without hiding behind fictitious names, both writers reveal personal stories centered on the inevitable conflict between father and son. The family theme brings them together while their behavior makes them different. The first part of our study, “The Rejected Father,” focuses on Hervé Guibert’s violent language and attitude towards his father he will never accept. The second part, “The Rejecting Father,” is an analysis of Yves Navarre’s struggle of reconciliation with his father disappointed by his sexual preferences.